Steel silo failure and reinforcement proposal. (May 2016) - Zaccari, Nicola; Cudemo, Michele
Abstract: Steel silo failure is not a sporadic event in the industrial field. Sometimes the failure involves only a shell deformation that does not affect the structural integrity of the overall silos. In other cases, failure involves complete collapse of the structure that could affect the people's safety. In general three major causes of silo failure are identified: design errors, construction errors, and utilization errors. In this study, a buckling failure of the real silos used in a thermal power plant to store a granular solid material (limestone) is analysed. It has long been recognized that the buckling failure of the silos is due mainly to the eccentric discharge of its stored solid. The main reason for this kind of failure is due to the difficulty, in the design phase, to characterize the pressure distribution caused by eccentric solids flow (funnelling). In the present study, the pressures caused by eccentric discharge are characterized using the new rules of the European Standard EN 1991-4 that defines the "Actions in Silos and Tanks". Using this new improved description of unsymmetrical pressures, it is now possible to perform relatively realistic calculations relating to this common but complicated shell buckling condition. The paper explores the structural behaviour leading to buckling during eccentric discharge and proposes a possible reinforcement design of the silos to minimize this kind of problems following the approach given in the European Standard EN 1993-1-6 "Strength and Stability of Shell Structures". Highlights: Detailed methodological approach for silo buckling calculation Reinforcement proposal for steel silos Eurocodes approach